Construction method of above ground level swimming pool / Muhammad Aminuddin Saidin - Saidin, Muhammad Aminuddin (Universiti Teknologi MARA, Perak, 2022)
A swimming pool is a water facility that is designed to hold water to a certain capacity in order for swimming or other leisure activities. Above ground level swimming pool types that used the glass wall has a lot of benefits to the owner and for the house itself in the context of the house surrounding. Therefore, this report briefly describes the construction of the above-ground level swimming pool. The objective of this report is to identify the construction method of above ground level swimming pool. In this report, a compressive explanation on the construction method started from the setting out until the testing and commissioning, including equipment, material, and the worker is described to give the overall view about the construction process. On top of that, the problems that occurred during the construction which represent the second objective also been stated along with the solutions to those problems. Three methods of study which is observation, unstructured interview and document review were applied as the data collection and references to achieve a detail explanation on the construction method of this swimming pool. Hope this report can provide knowledge to the reader about each construction method in order to construct the above ground level swimming pool.